The Blackwell companion to nineteenth-century theology. - Fergusson, David (Malden Wiley-Blackwell, 2010)
Bringing together a collection of essays by prominent scholars, this book presents a comprehensive account of the most significant theological figures, movements, and developments of thought that emerged in Europe and America during the 19th century.
pt. 1. Key thinkers and their influence. Kant / Nicholas Adams -- Schleiermacher / Christine Helmer -- Hegel / David Fergusson -- Coleridge / Stephen R. Holmes -- Kierkegaard / David R. Law -- Newman / Frank M. Turner -- pt. 2. Trends and movements. Natural science and theology / James C. Livingston -- Romanticism and pantheism / Julia A. Lamm -- Roamn Catholic theology : Tübingen / Bradford E. Hinze -- Russian theology / Olga Nesmiyanova -- Evangelicalism / David W. Bebbington -- Kenotic Christology / David R. Law -- Mediating anglicanism : Maurice, Gore, and Temple / Ulrike Link-Wieczorek -- Mediating theology in Germany / Matthias Gockel -- America : confessional theologies / James D. Bratt -- America : Transcendentalism to socail gospel / Robert W. Jenson -- Reformed theology in Scotland and in the Netherlands / Graham MacFarlane -- Neo-scholasticism / Ralph Del Colle -- The Bible and literary interpretation / Stephen Prickett -- Skeptics and anti-theologians / George Pattison -- History of religion school / Mark D. Chapman -- The Bible and theology / John W. Rogerson -- Liberal theology in Germany / Christine Axt-Piscalar -- Catholic modernism / Gerard Loughlin.
Keywords: Theology, Doctrinal -- History -- 19th century; 230.2 "18" -- Theologische scholen--(verder in te delen zoals 28)--19e eeuw. Periode 1800-1899; 23 <03> -- Dogmatiek. Systematische theologie. Theologie:--in strikte zin--Naslagwerken. Referentiewerken